2009
DOI: 10.1007/s00339-009-5454-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of calcium antimonate nano-crystals by the 18th dynasty Egyptian glassmakers

Abstract: During the 18th Egyptian dynasty (1570-1292 B.C.), opaque white, blue and turquoise glasses were opacified by calcium antimonate crystals dispersed in a vitreous matrix. The technological processes as well as the antimony sources used to manufacture these crystals remain unknown. Our results shed a new light on glassmaking history: contrary to what was thought, we demonstrate that Egyptian glassmakers did not use in situ crystallization but first synthesized calcium antimonate opacifiers, which do not exist in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 24 publications
4
40
0
2
Order By: Relevance
“…In regard to the production methods of Ca-antimonate in Roman glass, which hypothesize both in situ and ex situ crystallization [18], the present micro-textural features, such as the uneven distribution of crystals and the presence of relics of Ca-antimonate and rosary-shaped aggregates suggest that the ex situ method was used in PN TU1, PN TU2, PN TU3, PN CE1, PN AZ2, PN GR1, TN TU2, TN TU3, TN CE1, TN BO1, TN BIOP1, TN GR1 and TN VCH1. The same micro-structure was identified in Egyptian white, blue and turquoise opaque glass samples of the 18th Dynasty, for which ex situ crystallization is documented [48], although only rhombic phase was detected and not the only hexagonal one or a prevalence of it, as for the present assemblages. For the other tesserae from Pordenone and Trento with Ca-antimonate, showing euhedral crystals finely dispersed in the glass matrix (TN TU1, TN AQ1, TN AQ2, PN BO1, PN AZ1, TN AZ1, TN AZ2, PN BIOP1, TN GR2, PN VCH1), the hypothesis of in situ crystallization is more reliable.…”
Section: Turquoise Blue and White Tesseraesupporting
confidence: 56%
“…In regard to the production methods of Ca-antimonate in Roman glass, which hypothesize both in situ and ex situ crystallization [18], the present micro-textural features, such as the uneven distribution of crystals and the presence of relics of Ca-antimonate and rosary-shaped aggregates suggest that the ex situ method was used in PN TU1, PN TU2, PN TU3, PN CE1, PN AZ2, PN GR1, TN TU2, TN TU3, TN CE1, TN BO1, TN BIOP1, TN GR1 and TN VCH1. The same micro-structure was identified in Egyptian white, blue and turquoise opaque glass samples of the 18th Dynasty, for which ex situ crystallization is documented [48], although only rhombic phase was detected and not the only hexagonal one or a prevalence of it, as for the present assemblages. For the other tesserae from Pordenone and Trento with Ca-antimonate, showing euhedral crystals finely dispersed in the glass matrix (TN TU1, TN AQ1, TN AQ2, PN BO1, PN AZ1, TN AZ1, TN AZ2, PN BIOP1, TN GR2, PN VCH1), the hypothesis of in situ crystallization is more reliable.…”
Section: Turquoise Blue and White Tesseraesupporting
confidence: 56%
“…3B). Whether or not these differences point to different opacifying methods or reaction conditions cannot be decided at this stage (Lahlil et al, 2010b) as in both cases CaSb 2 O 6 was identified as the main opacifying phase. The opacifying crystals in the green and yellow samples are mostly lead antimonate in the form of bindheimite (Pb 2 Sb 2 O 7 ).…”
Section: Colourants Opacifiers and Microstructurementioning
confidence: 99%
“…2b,c), suggesting that they were precipitated from a soda-lime glass melt, as already reported in previous studies on Roman opaque glass dating from the 1st to the 4th centuries AD (e.g., Mass et al, 1998;Foster and Jackson, 2005;Wypyski and Becker, 2005;Lahlil et al, 2008Lahlil et al, , 2010avan der Werf et al, 2009;Gliozzo et al, 2010Gliozzo et al, , 2012 and also in Egyptian glass of the second millennium BC (e.g., Shortland, 2002). In all these studies, in situ crystallisation is the opacification process thought to be have been used to produce Ca antimonate, although a recent experimental study seems to support, for Egyptian glass, ex situ crystallisation and further intentional addition of the opacifier itself to translucent glass (Lahlil et al, 2010b). Some of the still open questions about in situ crystallisation are whether the source of antimony was natural stibnite (Sb 2 S 3 ) or roasted stibnite (a mixture of Sb 2 O 3 and Sb 2 O 4 ) and the crystallisation conditions of this phase, which show two modifications, hexagonal (CaSb 2 O 6 ) and orthorhombic (Ca 2 Sb 2 O 7 ).…”
Section: Calcium Antimonatementioning
confidence: 94%
“…One is the addition of natural or ex situ synthesised crystals to a transparent glass, and this type of opacifier is called primary. The other relies on the introduction of suitable raw materials which lead to in situ crystallisation of opacifying agents through separation from the melt, and is called secondary (Verità, 2000;Lahlil et al, 2010b). In this context, the opaque coloured glass tesserae from the chapel of St. Prosdocimus (Padova, Italy), dated to the 6th century AD (for more details on the historical background of the mosaic, see Silvestri et al, 2011b, and references therein), allowed us to carry out careful analytical study on the production technology of palaeo-Christian glass mosaic in a period known to be as crucial, due to the technological transition between the use of antimonybased opacifiers and that of tin-or phosphorus-based ones.…”
Section: Introductionmentioning
confidence: 99%